Boruto: Naruto next generations, Volume 15, The right job for idiots and bastards - Kodachi, Ukyo, 1979-; Kishimoto, Masashi, 1974- (Shonen Jump manga., 2022)
As the last remaining member of Kara, Code begins his plan for revenge against Boruto, Kawaki, and the others who took down Isshiki. His first move is to awaken an ally with a terrifying ability. Meanwhile, a determined Boruto has some plans of his own.